Flexible and broadband absorbing woven fabric using carbon-based resistive frequency selective surface. (1st April 2022) - Wang, Yuetang; Huang, Cheng; Peng, Jinqiang; Yuan, Liming; Qi, Yuzhuo; Luo, Xiangang
Abstract: In this paper, a flexible and broadband absorbing woven fabric with good mechanical property is proposed. It is composed of two-layer carbon-based resistive patterns printed on plain weave quartz fiber cloth, sandwiched by 3D woven fiber fabric through stitching process. An equivalent circuit model is introduced to guide the broadband absorption design. Both simulation and measured results have verified that such absorber can achieve −10 dB reflection bandwidth ranging from 7.1 to 35.4 GHz with the total thickness of 5.5 mm. The measured tensile strength reaches as high as 112 MPa, exhibiting the excellent mechanical performance compared with the traditional rubber absorbers. In addition, this absorber is also demonstrated to perform well under circumstances of oblique incidence and different polarizations. The above results suggest that our design is promising for the further development of novel flexible absorbers in wearable electronics and communication fields.